1990
DOI: 10.1111/j.2044-8260.1990.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal intent, hopelessness and depression in a parasuicide population: The influence of social desirability and elapsed time

Abstract: This paper reports the first British study to assess the construct validity of Beck's Hopelessness Scale (HS) and the Beck Depression Inventory (BDI). On the basis of interviews with 50 economically active parasuicide patients, it was confirmed that hopelessness accounts for the relationship between depression and suicidal intent. Moreover, it was shown that social desirability neither confounds the relationship between hopelessness and suicidal intent, nor has any predictive power in explaining variation in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 14 publications
1
33
2
1
Order By: Relevance
“…The finding that the association of self-reported hopelessness with suicide risk did not reach significance was also unexpected, since this has been a consistent finding demonstrated in a variety of studies over the past 40 years (Beck et al, 1985;McMillan et al, 2007;Salter & Platt, 1990). The most likely explanation for this anomaly (as well as being influential in the other nonsignificant effects) is that it was necessary to reduce the measure of suicide risk to a binary variable (zero vs. non-zero), thereby reducing the power of the regression analysis to adequately model variation in suicide risk.…”
Section: The Relationship Between Future-directed Thinking and Suicidmentioning
confidence: 59%
See 1 more Smart Citation
“…The finding that the association of self-reported hopelessness with suicide risk did not reach significance was also unexpected, since this has been a consistent finding demonstrated in a variety of studies over the past 40 years (Beck et al, 1985;McMillan et al, 2007;Salter & Platt, 1990). The most likely explanation for this anomaly (as well as being influential in the other nonsignificant effects) is that it was necessary to reduce the measure of suicide risk to a binary variable (zero vs. non-zero), thereby reducing the power of the regression analysis to adequately model variation in suicide risk.…”
Section: The Relationship Between Future-directed Thinking and Suicidmentioning
confidence: 59%
“…Self-reported hopelessness has been shown to predict suicidal ideation, DSH and suicide completion in numerous studies (Beck, Steer, Kovacs, & Garrison, 1985;McMillan, Gilbody, Beresford, & Neilly, 2007;Petrie, Chamberlain, & Clarke, 1988;Salter & Platt, 1990;Zhang & Li, 2013). Furthermore, self-reported hopelessness has been shown to mediate the relationship between depression and suicide: a stronger relationship is found between measures of hopelessness and suicide behaviour than between measures of depression and suicide behaviour Beck et al, 1985;Minkoff, Bergman, Beck, & Beck, 1973).…”
Section: Overview Of Hopelessnessmentioning
confidence: 99%
“…Moreover, global hopelessness mediates the relationship between depression and suicidality (Salter & Platt, 1990), as well as predicting suicidal repetition (Petrie et al,1988) and completed suicide (Beck et al, 1989). However, up until the 1990s (MacLeod et al, 1993) it was not clear which components of pessimism for the future were most pernicious.…”
Section: Hopelessness Future Expectancies and Suicidalitymentioning
confidence: 99%
“…Previous research has found that hopelessness is a critical factor in increasing the risk of suicidal behavior (Salter & Platt, 1990;Wetzel, Margulies, Davis, & Karam, 1980). Hopelessness is closely associated with whether individuals feel they have any reasons for living (Linehan, Goodstein, Nielsen, & Chiles, 1983;Malone, Oquendo, Haas, Ellis, Li, & Mann, 2000;Mann et al, 1999) and predicts both repetition of suicide attempts (Mann et al, 1999;Petrie, Chamberlain, & Clarke, 1988;Scott, House, Yates, & Harrington, 1997;Sidley, Calam, Wells, Hughes, & Whitaker, 1999;Szanto, Reynolds, Conwell, Begley, & Houck, 1998) and completed suicides up to 10 years later (Beck & Steer, 1989;Beck, Brown, Berchick, Stewart, & Steer, 1990;Fawcett et al, 1990).…”
Section: Introductionmentioning
confidence: 99%